Jet and jet-mixing grouting - Krysan, Volodymyr; Krysan, Vitaliy (Academic journal Industrial Machine Building Civil Engineering, 2018)
Analysis of ground cement elements production technologies by jet, jet mixing and mixing technologies with the consumption of various quantities of cement needed for their manufacture is carried out, their applicability is determined. It has been defined that design of bases and building bases grouted by ground-cement elements on weak and subsidence soils requires scientific approach. Mixing and jet-mixing technologies are more cost-effective ones and do not require pulp utilization; the material (ground cement) obtained during soils jet grouting for determining change in its characteristics in time and under the influence of various factors should be studied.
Keywords: ground cement; ground cement elements; cementation; fixing solutions; building bases; technologies